Technical-tactical demands of 3 × 3 international basketball games according to game outcome, player sex, and competition phase - Ferioli, D.; Conte, D.; Scanlan, A. T.; Vaquera, A. (The Journal of Strength and Conditioning Research, 2023)
Despite the popularity of 3 × 3 basketball rapidly growing on a global scale, a paucity of data exist on player demands during competition, particularly considering various factors. This study aimed to quantify the technical-tactical demands of international-level 3 × 3 basketball games according to game outcome, player sex, and competition phase. Overall, 96 players from 24 national teams (48 players across 12 teams in each sex) competing at the 2019 European Basketball Cup 3×3 were included in this study. Technical-tactical demands during games including shooting, game-related, and possession-related statistics were retrospectively gathered from public sources or analyzed using video analyses. Linear mixed models and effect size analyses were used to determine differences in demands according to game outcome (wins vs. losses), player sex (males vs. females), and competition phase (group games vs. finals games). Winning teams (p < 0.05, small-large) scored more shots, shot more efficiently, secured more rebounds, committed fewer turnovers and fouls, and drew more fouls to shoot free-throws. Differences between sexes (p < 0.05, small-moderate) showed male teams shot more efficiently, scored more 2-point shots, and scored more points, whereas female teams attempted more 1-point shots, committed more turnovers, and had more possessions. Considering the competition phase, more blocks were completed during group games, and more points per possession were achieved during finals games (p < 0.05, small). This study provides foundation normative values regarding the technical-tactical demands of 3 × 3 game-play during an international competition, with reported data able to be used by practitioners in developing precise, sex-specific training and tactical strategies to optimize team success.